The Liversidge nugget collection: a new look at some old gold - Butt, C.; Timms, Nicholas Eric (Taylor & Francis Co Ltd, 2011)
Archibald Liversidge FRS (University of Sydney 1874–1907) had a long-term interest in the origin of gold nuggets, a matter of considerable contemporary debate. He conducted pioneering studies on the petrography of nuggets, noting their polycrystalline structure. This supported his earlier conclusion, based on chemical and geological field evidence, that most, if not all, nuggets were hypogene. However, these petrographic studies and his conclusions were forgotten within 40 years. Liversidge bequeathed his collection of prepared specimens of nuggets, crystals and manufactured gold to the British Museum. The collection includes many of those featured in his publications, and their state of preservation is such that they can be examined by optical and scanning electron microscopy without further preparation. This paper illustrates some of the specimens and describes aspects of their composition and microstructure using modern characterisation techniques that re-affirm and advance his conclusions regarding their hypogene origin. The last nuggets that Liversidge described, from New Guinea, he considered unusual in that they display no obvious crystal structure but are zoned—a feature then and now commonly considered to be a potential indicator of a supergene origin. However, scanning electron microscope, electron microprobe and electron back-scattered diffraction analyses of one of these nuggets show the zonation to be chemical (6–25 wt% Ag) and that it contains Ag–Au–Hg telluride inclusions, and confirm that it consists of a single crystal. These observations are consistent with a hypogene, probably epithermal, origin, with the gold having been precipitated in a cavity, and not subsequently re-crystallised or annealed.